Pemenuhan Kesejahteraan Karyawan dan Dampaknya terhadap Produktivitas dan Loyalitas Karyawan di Semarang - Widia Roker (Lembaga Pengembangan Kinerja Dosen, 2026)
Employee welfare is an issue that is often highlighted, whether by individuals as employees, researchers, academics, or even governments. In the business aspect, neglected welfare has a great effect on employee productivity and loyalty to the company, so this study is aimed at examining the impact of fulfilling employee welfare on employee productivity and loyalty to the company. This study uses a qualitative method with a case approach and uses interviews as a data collection instrument. This study shows that of the five informants, they admitted that the company has provided decent welfare, even though there are still some things that are forgotten, ignored, and can be improved and improved. Five informants admitted that the welfare they get has a great effect on their productivity and loyalty to the company, 2 out of 5 informants even added that the reason they have survived to this day is not because of the welfare they get, but because there is no other choice.